Carbon Nanofiber Synthesis within 3-Dimensional Sintered Nickel Microfibrous Matrices: Optimization of Synthesis Conditions - Amogh N. Karwa; Virginia A. Davis; Bruce J. Tatarchuk (Journal of Nanotechnology)
This study focuses on the process of optimization for carbon nanofiber synthesis at the exterior and the interior of 3-dimensional sintered nickel microfibrous networks. Synthesis of carbon nanofibers (CNF) by catalytic decomposition of acetylene (ethyne) was conducted at atmospheric pressure and short reaction times (10 min). Two factors evaluated during the study were (a) CNF quality (observed by SEM and Raman spectroscopy) and (b) rate of reaction (gravimetrically measured carbon yield). Independent optimization variables included redox faceting pretreatment of nickel, synthesis temperature, and gas composition. Faceting resulted in an 8-fold increase in the carbon yield compared to an untreated substrate. Synthesis with varying levels of hydrogen maximized the carbon yield (9.31 mg C/cm2 catalyst). The quality of CNF was enhanced via a reduction in amorphous carbon that resulted from the addition of 20% ammonia. Optimized growth conditions that led to high rates of CNF deposition preferentially deposited this carbon at the exterior layer of the nickel microfibrous networks (570°C, 78% H2, 20% NH3, 2% C2H2, faceted Ni.). CNF growth within the 3-dimensional nickel networks was accomplished at the conditions selected to lower the gravimetric reaction rate (470°C, 10% H2, 88% N2, 2% C2H2, nonfaceted Ni).